Increased Serum Sclerostin Levels in Patients With Active Acromegaly - Pekkolay, Zafer; Kilinc, Faruk; Gozel, Nevzat; Onalan, Ebru; Tuzcu, Alpaslan Kemal (Endocrine Soc, 2020)
Context: Bone mineral density is normal in acromegalic patients and the cause of increased fracture risk that characterizes active acromegaly is unknown. Objective: This study compared serum sclerostin levels between patients with active acromegaly and healthy individuals. Design, Setting, and Participants: The serum sclerostin levels of patients with active acromegaly were compared with those of healthy volunteers in a cross-sectional study. The mean age of the 30 acromegaly patients (male/female: 14/16) was 47.26 +/- 12.52 years (range, 18-64 years) and that of the healthy volunteers (male/female: 17/13) was 44.56 +/- 10.74 years (range, 19-62 years). IGF-1 and GH levels were measured using an electrochemiluminescence method, and serum sclerostin levels using an ELISA. The Mann-Whitney U test was used to compare sclerostin levels between the 2 groups. The correlations of sclerostin level with IGF-1 and GH were determined using Spearman's test. Results: The 2 groups did not differ in age or sex (P > 0.05). The median GH and IGF-1 levels in the patient group were 2.49 ng/mL (range, 0.22-70.00 ng/mL) (interquartile range [IQR], 1.3-4.52) and 338.5 ng/mL (range, 147-911 ng/mL) (IQR, 250-426), respectively. The median GH and IGF-1 levels in the control group were 0.95 ng/mL (range, 0.3-2.3) and 144 ng/mL (range, 98-198), respectively. The median sclerostin level was 29.95 ng/mL (range, 7.5-78.1 ng/mL) (IQR, 14.37-37.47) in the acromegaly group and 22.44 ng/mL (range, 8.45-36.44 ng/mL) (IQR, 13.71-27.52) in the control group (P < 0.05). There was a moderate positive correlation between the sclerostin and IGF-1 levels (rho = 0.54; P < 0.01), and between the sclerostin and GH levels (rho = 0.41; P < 0.05). Conclusions: High sclerostin levels may contribute to the increased fracture risk seen in patients with acromegaly.
Keywords: sclerostin; acromegaly; osteoporosis